A STUDY OF GRASSROOTS DEMOCRACY IN INDIA: ROLE OF PANCHAYATI RAJ INSTITUTIONS - Nutan (ShodhKosh: Journal of Visual and Performing Arts, 2023)
This paper explores the role of Panchayati Raj Institutions (PRIs) in the development of grassroots democracy in India. Since their constitutional establishment in 1992, PRIs have been a crucial mechanism for decentralizing power, ensuring local self-governance, and fostering inclusive participation in decision-making processes. This study examines the evolution, functioning, and challenges faced by PRIs at various levels—village, intermediate, and district. By analyzing empirical data, legislative frameworks, and case studies from different states, the paper assesses how PRIs have contributed to democratic deepening, social equity, and empowerment of marginalized communities, especially women and Scheduled Castes. However, it also highlights persistent issues such as inadequate financial autonomy, political interference, and the limited capacity of local leaders. The research emphasizes the need for structural reforms, enhanced capacity-building, and greater empowerment to fully realize the potential of Panchayati Raj as a tool for strengthening grassroots democracy in India. Ultimately, the paper provides recommendations for improving the effectiveness of PRIs in achieving sustainable development and participatory governance at the local level.